Inovasi Pengelolaan Manajemen Sarana dan Prasarana Pendidikan dalam Meningkatkan Quality Proses Pembelajaran di SMAN 1 Kandangan - Hunainah, Tsamrotul; Rosyidi, Muhammad (UIN Mahmud Yunus Batusangkar, 2025)
The existence of educational facilities is absolutely necessary in the educational process, so it is included in the components that must be fulfilled in the implementation of the educational process. This research report presents an innovation in planning the management of facilities and infrastructure (sarpras) at this school which is certainly carried out with clear and orderly steps. First of all, everything starts with planning. With routine and directed supervision, the facilities and infrastructure at SMAN 1 Kandangan are maintained and support the creation of a comfortable and quality learning environment. It is hoped that an understanding of the facilities and infrastructure management process at SMAN 1 Kandangan includes three main stages: planning, direction, and supervision. Planning is carried out in a thorough and participatory manner, involving all elements of the school, and focusing on budget efficiency and transparency according to the RKAS.